Devise, Extend and Upgraded Algorithm of Gene Sequence for Local Alignment (International Journal of Engineering and Computer Science, 2013)
Finding similar regions from two strings or nucleotides or protein sequences is very much desirable for determining the functional similarity between them. In the ground of bioinformatics, for determining analogous constituency between two sequences, sequence-alignment can be used, which is the way of arranging sequences. This can also be helpful for non-biological field such as natural language processing or financial data. Finding out the larger sequence from the dissimilar sequences those are suspected to contain regions of similarity motifs within their long sequence context, local-alignment (maximum length exact matching) is very useful which mostly works on identifying the best pair of regions. In this research work an innovative method is proposed for searching bio-sequences/genesequences for the local alignment. This paper also provides an evaluation of the proposed algorithm and turns a black and white comparison with one of the popular existing methods and a modified version of the existing method. The evaluation result shows that the existing method is very time and space/memory consuming where the promising approach of projected technique is to seek out the identical sequences by taking less computational time and using less memory space. Therefore, we have faith that the new era of searching similar region from sequences is going to be raised for this proposed innovative method.